Annuities : Regulating Withdrawals from Individual Pension Accounts - World Bank (Washington, DC, 2012)
Pension, to most people, implies a regular payment from a specific age-such as retirement-until death. Individual retirement accounts are a vehicle for retirement savings but they do not become a pension in the conventional sense of the word until they are converted to an 'annuity'. How much and what type of annuitization should be mandated are key policy questions facing reformers. Economists believe that annuities can make people better off. The intuition is straightforward. Life expectancy is normally uncertain. So people would have to spend accumulated wealth slowly after retirement to ensure an adequate income should they live a long time. This kind of self-insurance is costly because it increases the chances that people will consume less than they could have if they knew when they were going to die. This cost can be reduced with annuities, which pool risk across individuals.